Проблематика використання сгенерованим штучним інтелектом зображенням як референсу - Носенко, Д. М. (ХНУРЕ, 2025)
The use of AI-generated images as references is becoming increasingly popular in contemporary digital art and design, giving artists quick access to unique visual solutions. However, this approach brings with it a number of challenges, including distortion of anatomy and perspective, stylistic instability, difficulties in meeting professional standards, and copyright uncertainty. Generative neural networks create images based on huge amounts of data, which can lead to the use of other people's artistic styles without permission. They also do not take into account the compositional logic and physics of objects, which re quires manual correction. Therefore, it is important to investigate the problems and limitations of using such images in the creative process to determine their effectiveness and ways to minimise risks.
Keywords: AI-generated images; референс